Worldwide Military Spending, 1990-1995 - Schiff, Jerald (IMF Working Papers; Working Paper ;, 1996)
The decline in military spending that began in the mid-1980s continued through 1995, and this decline was widespread both geographically and by level of development. Cuts in military spending appear to have potentially important implications for nonmilitary spending and fiscal adjustment. In contrast to findings for previous periods, military spending has declined more than proportionately in those countries that have reduced total spending. Countries with Fund programs have reduced military spending more sharply than other developing countries, largely reflecting outcomes in the transition economies. Further, military spending appears to have been less resilient in program countries than other developing countries.